PENGARUH MODEL KNOW WANT LEARNING TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN TEKS BERITA ELEKTRONIK - Nana Triana Winata; Embang Logita (Jurnal Semantik, 2023)
This research is motivated by students lack of interest in reading, this affects the level of reading comprehension of students who do not understand the content/information obtained in the reading text. This study aims to (1) determine students reading ability using convensional strategies; (2) test the ability to read and understand electronic news text using the KWL model; and (3) know the effect of the KWL model on students ability in reading comprehension of electronic news text. This study uses experimental research methods, this method requires a special treatment which aims to find the effect of one variable on another variable. The design used is in the form of Nonequivalent control group design. The results of this study, both in the pretest and posttest there was an increase in the average score obtained by students 85,33. Thus value has exceeded the standard passing grade in Indonesian subjects, which is 75. The results of data processing using SPSS obtained is an effect of using the KWL model on the ability to read comprehension of electronic news text in class XII-IPS 2 MAN Indramayu.